Investigation of groundwater table distribution using borehole piezometer data interpolation : case study of Singapore - Nistor, Margarit Mircea (2021)
The variation of groundwater table is important information for Civil Engineering and related practices. The most appropriate datasets for the groundwater table mapping are the water level measurements in borehole piezometers. The methods for development of the groundwater table distribution on a continuous surface are affected by the hydrological factors and spatial variability of the soils. In this study, the piezometer data of the groundwater table in soils from four formations in Singapore were used to predict the continuous surface of the groundwater table. The interpolation of groundwater table elevation was performed using geostatistical analyses: inverse distance weighted (IDW) and Ordinary Kriging (OK) interpolations within residual soils from Bukit Timah Granite Formation, Old Alluvium Formation, Jurong Formation, and Kallang Formation. The interpolations were completed based on 80% of dataset (1,282 piezometers for wet season and 2,567 piezometers for dry season). The evaluation of the predicted groundwater table maps was carried out using cross-validation method (CVM) based on 20% of the datasets (256 piezometers for wet season and 512 piezometers for dry season). The results show that the IDW and OK interpolations generated quite similar predictions of the groundwater table distribution ranging between -3.7 m and 58 m elevation with respect to sea level, depending on hydrogeological conditions and soil formation characteristics. The validation method indicated a very good performance of IDW and OK in predicting the groundwater table distribution in Singapore (r2 > 0.8). The proposed procedures and methodologies covering the interpretation of data from piezometers, spatial analyses and evaluation of groundwater table map via geographical information system (GIS) approach presented in this paper will benefit Civil Engineers prior to building construction. The developed groundwater table map will be useful to determine the optimum number of piezometers still required for designs, to design the low cost and effective ground improvement, foundation and retaining wall in order to ensure the stability of the building during and after the completion of the project.